PROPOSIÇÃO DE AÇÕES PARA POTENCIALIZAÇÃO DA CAPTAÇÃO DE RECURSO FINANCEIRO EM UMA INSTITUIÇÃO PÚBLICA DE ENSINO PROFISSIONAL JUNTO À INICIATIVA PRIVADA - Cao, Elimara do Rosario (2022)
The search for alternative sources of funding in public education, in a scenario of cutting public investment, is a challenging action, whether the capture in the public or private sphere. Among the possibilities, the legislation points to the capture of resources through actions aimed at stimulating innovation and technological and scientific production, through partnership with public or private organizations. In this sense, additional public investments have been made in the sector, but still insufficient. On the other hand, the inexecution or low funding of financial resources from the private sector is an incipient practice in professional public education, which raised the question of the question: What actions to propose to enhance the capture of financial resources on a campus of a public institution of professional education with the private sector? Having as main objective to propose actions to enhance the capture of financial resources between a campus of an Institution of the Federal Network of Professional Education (IRFEP) and the private initiative, the role of Professional Education Institutions and their relationship with the private initiative, the management of the capture of external resources in public educational institutions, was addressed in theoretical terms, the law of innovation and the private partnership in Brazilian professional education and the foundation's performance of support in professional education. Regarding scientific methods, the research was carried out with a qualitative, exploratory and descriptive approach of the relationship between a campus of the federal network of professional education and the private initiative, using the current reality tree to identify the cause-effect relationships of the process of non-execution of partnerships with financial transfer and having through data sources: documentary collection of the processes of partnerships with the market in the period 2020 to 05/2021, mediated by the support foundation, bibliographic survey, benchmarking, interviews and non-participant observation to answer the problem. The results of the literature review demonstrated that entrepreneurship practices, technology transfer, donations, cost sharing, aligned with technology can enhance the collection of financial resources. However, obstacles such as insufficient human resources and low qualification for interaction with actors in the academic ecosystem reduce school-company interaction. Thus, as a technical product, a Conclusive Technical Report was presented, with the proposition of an action plan for improvements in the partnership process with the market, in order to enhance the capture of financial resources and increase the school-company interaction for a campus of a federal professional education institution.